Multimodal Analysis of Augmented Reality in Basic Programming Course: Innovation Learning in Modern Classes - Wulansari, Rizky Ema; Sakti, Rizki Hardian; Saputra, Hasep; Samala, Agariadne Dwinggo; Novalia, Rifyal; Tun, Hla Myo (Journal of Applied Engineering and Technological Science (JAETS), 2024)
The purpose of this research was to examine the effectiveness of Augmented Reality when implemented as a modern approach in a basic programming course, to solve problems in learning abstract concepts of programming. This vision places AR as a rich solution to programming education in the digital era, given the potential of the medium in delivering a deeper understanding of programming constructs in the context of complex and engaging visualizations. In this experimental study, a multimodal analysis and the ASSURE model were used in incorporating AR in a contemporary classroom. There were 61 students who took the basic programming course for students and all of them were included in the study. Self-completed questionnaires were used to record the impact of AR on the students, specifically on the understanding of the concept, motivation to learn and learning engagement. The study brought out the following key discovery; Ar enhanced students’ comprehension of the basic concepts in programming, enhanced their interest and encouraged them through the creative design of the learning process. AR enhanced some aspects of programming elucidated by student, particularly turning the complex programming strategy into an easily manageable model as well as providing for a real-time simulation and graphical rendering, all of which were difficult. Still, and importantly, AR cut down on mistakes and provided a clear understanding of the coding patterns Iraq required. Applying AR into the learning of programming education has practical implications in improving students learning experiences as well as simplifying existing concepts. In theory, this work entails the effectiveness of Augmented Reality in programming education and the exploration of opportunities for application of new ideas in technology-enabled teaching in the information age.